Optimizing Assisted Reproductive Techniques: The Role of L-Carnitine, Acetyl-L-Carnitine, and IMSI in Managing High-Sperm DNA Fragmentation - Chitra Kamble; Aakash More; Sudhanshu Dakre (Journal of Pharmacy and Bioallied Sciences)
This case reports a couple with infertility due to male factor asthenozoospermia and increased sperm DNA fragmentation along with a slightly thin endometrial lining of the female partner. The male partner received 1 g/day of acetyl-L-carnitine and 2 g/day of L-carnitine for 3 months, following which sperm motility was improved, and DFI was reduced from 45% to 20%. Intracytoplasmic morphologically selected sperm injection (IMSI) was utilized during the in vitro fertilization (IVF) cycle to utilize sperms with optimal morphological characteristics for fertilization selectively. To improve endometrial receptivity, the female partner underwent estrogen and platelet-rich plasma (PRP) treatment and the endometrial thickness increased from 6.5 mm to 8 mm, improving endometrial receptivity. A frozen embryo transfer was then carried out after 1 month of the initial cycle. Two weeks after the transfer, a subsequent serum β-hCG level measured 302 mIU/mL, indicating a pregnancy. This case demonstrates the importance of the combined management of acetyl-L-carnitine and L-carnitine supplementation alongside IMSI and PRP in treating the complex etiology of both male and female infertility and leading to successful IVF pregnancy. The systematic approach to focus on aspects that included improving sperm quality as well as the endometrium was therefore important in yielding the result.